The impact of complex engineering and geological conditions on the durability of the polymer pipeline - Aleksandrovych, Vadym; Havryliuk, Olha; Sukhov, Valeriy (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2022)
Formulation of the problem. During the construction of the oil collector, in order to ensure uninterrupted transportation of products, it was planned to lay an industrial oil collector made of fiberglass pipes. In some areas, repeated depressurization of the joints of the fiberglass oil collector occurred. In this regard, there was a need for a comprehensive approach to establishing the causes of the aerial situations. The purpose of the article is to analyze the impact of complex engineering and geological conditions on the durability of the polymer pipeline using the example of an industrial oil collector made of fiberglass pipes of the Anastasiv deposit, located in the territory of the Romen district of the Sumy region of Ukraine. Materials and methods. To achieve the goal, a visual survey of the geological and geomorphological structure was performed, as well as the analysis of the engineering and geological conditions of the territory where the fiberglass pipeline is laid. Soil samples were taken from the place of depressurization of the polymer pipeline joint, and their physical and mechanical characteristics were determined. Modeling and calculation of the stability of the slope on which the depressurization of the joint of the polymer pipeline occurs, were carried out by the finite element method. Results. During the examination of the fiberglass pipeline, negative and potentially negative factors of the engineering and geological conditions influence on the laying and operation of fiberglass collectors were established. It was revealed that there was a discrepancy between the design decision and the actual layout of the fiberglass pipes, which could lead to the occurance of areas of "sag" and, as a result, an increase in the stresses in the pipeline from the backfill load. At the same time, the realization of subsidence phenomena of IGE 5 after laying the pipeline also led to additional non-design stresses. The analysis of engineering-geological and hydrogeological conditions indicates the possible activity of slope processes in the study area, which leads to a violation of the stability of the slope and, consequently, the occurrence of additional displacement and stresses due to,deformation of the soil massif. Scientific novelty and practical significance. The necessity of conducting engineering-geological surveys to assess the impact of complex engineering and geological conditions on the durability of a polymer pipeline is substantiated. The main negative processes and phenomena that led to emergency situations on the territory of laying the polymer pipeline were identified.